BOOSTING LIFELONG LEARNING FOR GENERAL SECONDARY SCHOOLTEACHERS: DIGITAL COMPETENCE DEVELOPMENT AMID BLENDED LEARNING - Malykhin, Oleksandr; Aristova, Nataliia; Alieksieieva, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The research is targeted at examining general secondary schoolteachers’ strategies for assessing, self-assessing and improving their digital competence. The authors also define the scope of the most effective strategies for developing schoolteachers’ digital competence amid blended learning caused by the Covid-19 pandemic. The main aim of research is to clarify the most effective ways of improving schoolteachers’ digital competence amid blended learning caused by the Covid-19 pandemic. The research activities have been organized and realized taking into account the undisputable fact that digital competence is the key one for lifelong learning. The research methodology for generalizing theoretical material and empirical data collecting implies combining theoretical (analysis and synthesis) and empirical (a web-based questionnaire, individual interviews, conversations with respondents and analysis of reflexive texts) methods of investigation. The research sample consists of 1284 general secondary schoolteachers from different regions of Ukraine. The authors examine information obtained by using the mentioned combination of empirical methods of investigation. As a result of research some certain strategies for developing schoolteachers’ digital competence are found out, described and recommended for being implied into both the system of general secondary school education and the system of general secondary schoolteachers’ postgraduate education. It is also proved that the process of developing general secondary schoolteachers’ digital competence amid blended learning organized effectively is the basis for boosting their further lifelong learning.